Konstelasi Islam Wasathiyah dan Pancasila Serta Urgensinya Dalam Bernegara Perspektif Maqasid al-Syari’ah - Umi Kulsum (Journal of Islamic Civilization, 2020)
Pancasila as the basic ideology of the Unitary Republic of Indonesia is the final consensus. But behind this, groups emerged that sought to clash between Pancasila and Islamic teachings. There are even groups that explicitly state that Pancasila is the taghout, contrary to Islamic teachings. Of course this is a conclusion that is too hasty. Therefore, the author tries to explain how the correlation between Pancasila with the source of Islamic teachings (al-Qur'an) through the maqasid approach to sharia. Through this approach, the author concludes that all precepts contained in Pancasila actually substantially nothing contradictory to the verses of the Qur'an. In fact, all of the precepts have the same spirit as the Qur'an. Pancasila, Maqasid al-Syariah, thagut